Software engineering based self-checking process for cyber security system in VANET - Muntadher Naeem Yasir; Muayad Sadik Croock (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Newly, the cyber security of Vehicle Ad hoc Network (VANET) includes two practicable: Vehicle to Vehicle (V2V) and Vehicle to Infrastructure (V2I), that have been considered due to importance. It has become possible to keep pace with the development in the world. The people safety is a priority in the development of technology in general and particular in of VANET for police vehicles. In this paper, we propose a software engineering based self-checking process to ensure the high redundancy of the generated keys. These keys are used in underlying cyber security system for VANET. The proposed self-checking process emploies a set of NIST tests including frequency, block and runs as a threshold for accepting the generated keys. The introduced cyber security system includes three levels: Firstly, the registration phase that asks vehicles to register in the system, in which the network excludes the unregistered ones. In this phase, the proposed software engineeringbased self-checking process is adopted. Secondly, the authentication phase that checks of the vehicles after the registration phase. Thirdly, the proposed system that is able to detect the DOS attack. The obtained results show the efficient performance of the proposed system in managing the security of the VANET network. The self-checking process increased the randomness of the generated keys, in which the security factor is increased.